Case report: Multimodal imaging diagnosis of a giant coronary artery fistula: A report of two cases - Sharifkazemi, Mohammadbagher; Mohseni-Badalabadi, Reza; Hosseinsabet, Ali; Hajizeinali, Alimohammad (Frontiers in Cardiovascular Medicine, 2022)
Being a very rare cardiac disease, most cases of coronary artery fistula (CAF) are genetic. Complications such as coronary steal syndrome, myocardial infarction, heart failure, or tamponade can manifest following the abnormal communication that the fistula creates between the coronary arteries and cardiac chambers or major vessels and the subsequent shunt. Most CAFs are small and asymptomatic, making diagnosis difficult. In symptomatic patients, the initial diagnostic workup is generally made with chest radiography and electrocardiography. Other imaging modalities have also been suggested to improve diagnostic accuracy. Cardiac catheterization and coronary angiography are currently the gold standard for diagnosis and planning the intervention, as they can recognize the quantum of the shunt as well as complications of a fistulous track (e.g. aneurysm formation, thrombus, leak, and the number of openings to the receiving chamber/vessel); however, this invasive method may be associated with risk. Herein, we report two patients with giant CAFs, one from the left circumflex artery to the coronary sinus and the other to the superior vena cava. Moreover, we describe how multimodal imaging, including two- and three-dimensional transesophageal echocardiography, coronary cineangiography, coronary computed tomography angiography, and enhanced chest computed tomography, can facilitate diagnosis and estimate the disease course in such patients. We believe that using multimodal imaging can not only help the initial diagnosis regarding the presence of a CAF and the accurate anatomical site of the fistula in the patient but can also help predict the disease course and choose the most suitable treatment modality. Therefore, we suggest multimodal imaging be done to diagnose patients suspected of CAF. However, invasive cineangiography should be necessarily followed, regardless of whether an intervention is planned or not.